Long-term secondary prevention of cardiovascular disease with a Mediterranean diet and a low-fat diet (CORDIOPREV): a randomised controlled trial. Issue 10338 (14th May 2022) - Delgado-Lista, Javier; Alcala-Diaz, Juan F; Torres-Peña, Jose D; Quintana-Navarro, Gracia M; Fuentes, Francisco; Garcia-Rios, Antonio; Ortiz-Morales, Ana M; Gonzalez-Requero, Ana I; Perez-Caballero, Ana I; Yubero-Serrano, Elena M; Rangel-Zuñiga, Oriol A; Camargo, Antonio; et al.
Summary: Background: Mediterranean and low-fat diets are effective in the primary prevention of cardiovascular disease. We did a long-term randomised trial to compare the effects of these two diets in secondary prevention of cardiovascular disease. Methods: The CORDIOPREV study was a single-centre, randomised clinical trial done at the Reina Sofia University Hospital in Córdoba, Spain. Patients with established coronary heart disease (aged 20–75 years) were randomly assigned in a 1:1 ratio by the Andalusian School of Public Health to receive a Mediterranean diet or a low-fat diet intervention, with a follow-up of 7 years. Clinical investigators (physicians, investigators, and clinical endpoint committee members) were masked to treatment assignment; participants were not. A team of dietitians did the dietary interventions. The primary outcome (assessed by intention to treat) was a composite of major cardiovascular events, including myocardial infarction, revascularisation, ischaemic stroke, peripheral artery disease, and cardiovascular death. This study is registered with ClinicalTrials.gov, NCT00924937 . Findings: From Oct 1, 2009, to Feb 28, 2012, a total of 1002 patients were enrolled, 500 (49·9%) in the low-fat diet group and 502 (50·1%) in the Mediterranean diet group. The mean age was 59·5 years (SD 8·7) and 827 (82·5%) of 1002 patients were men. The primary endpoint occurred in 198 participants: 87 in the Mediterranean diet group and 111 in the low-fat group (crude rate per 1000 person-years: 28·1 [95% CI 27·9–28·3] in the Mediterranean diet group vs 37·7 [37·5–37·9] in the low-fat group, log-rank p=0·039). Multivariable-adjusted hazard ratios (HRs) of the different models ranged from 0·719 (95% CI 0·541–0·957) to 0·753 (0·568–0·998) in favour of the Mediterranean diet. These effects were more evident in men, with primary endpoints occurring in 67 (16·2%) of 414 men in the Mediterranean diet group versus 94 (22·8%) of 413 men in the low-fat diet group (multiadjusted HR 0·669 [95% CI 0·489–0·915], log-rank p=0·013), than in 175 women for whom no difference was found between groups. Interpretation: In secondary prevention, the Mediterranean diet was superior to the low-fat diet in preventing major cardiovascular events. Our results are relevant to clinical practice, supporting the use of the Mediterranean diet in secondary prevention. Funding: Fundacion Patrimonio Comunal Olivarero; Fundacion Centro para la Excelencia en Investigacion sobre Aceite de Oliva y Salud; local, regional, and national Spanish Governments; European Union.